2006
DOI: 10.4049/jimmunol.177.11.7913
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Individual Contributions of Igα (CD79a)- and Igβ (CD79b)-Mediated Tonic Signaling for Bone Marrow B Cell Development and Peripheral B Cell Maturation

Abstract: The individual contribution of Igα and Igβ for BCR-triggered fates is unclear. Prior evidence supports conflicting ideas concerning unique as well as redundant functions for these proteins in the context of BCR/pre-BCR signaling. Part of this ambiguity may reflect the recent appreciation that Igα and Igβ participate in both Ag-independent (tonic) and Ag-dependent signaling. The present study undertook defining the individual requirement for Igα and Igβ under conditions where only ligand-independent tonic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 97 publications
1
16
1
Order By: Relevance
“…In the absence of ligand stimulation, BCR basal signaling is essential for survival (33) and differentiation (34). Monroe and colleagues showed that the cytoplasmic tails of Iga and Igβ in the absence of Ag binding are sufficient to drive FO B2 but not MZ and B1 cell differentiation (34, 35). Consistent with this finding, Hayakawa et al (36) showed that immature B cells expressing a transgenic BCR specific for the self Thy-1 glycoprotein develop into FO B2 cells in the absence of Thy-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of ligand stimulation, BCR basal signaling is essential for survival (33) and differentiation (34). Monroe and colleagues showed that the cytoplasmic tails of Iga and Igβ in the absence of Ag binding are sufficient to drive FO B2 but not MZ and B1 cell differentiation (34, 35). Consistent with this finding, Hayakawa et al (36) showed that immature B cells expressing a transgenic BCR specific for the self Thy-1 glycoprotein develop into FO B2 cells in the absence of Thy-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, published work has shown that peripheral B cell survival is absolutely dependent on low-level “tonic” signaling through the B cell receptor (Bannish et al, 2001; Lam et al, 1997) and that even naïve B cells have low-level activation of the Igμ signaling pathway (Fuentes-Panana et al, 2006). It is possible that Igμ-mediated tonic signaling, along with the elevated levels of soluble and/or cell-associated CD40, TLR ligands and cytokines present in inflammatory disease patients (Al-Attas et al, 2009; Cani et al, 2007; Creely et al, 2007; Jinchuan et al, 2004; Liu et al, 1999; Varo et al, 2003), are sufficient to induce B cell TLR4 activation in vivo, even in the absence of the activation history that characterizes the memory compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike CD20, CD79α and CD79β have important signaling functions for B cells as they couple to MHC II and BCR (19) and initiate downstream tyrosine phosphorylation and intracellular release of Ca 2+ . It is appreciated that CD79α (Igα) and CD79β (Igβ) participate in both Ag-dependent and Ag-independent signaling (20). Thus, unlike anti-CD20, anti-CD79 Abs might have dual functions in vivo.…”
Section: Discussionmentioning
confidence: 99%